A Training Needs Analysis Case Study at Legal Aid Queensland - Davies, Claudia; Vankoningsveld, Richard (Evidence Based Library and Information Practice, 2015)
Abstract Objective – Legal Aid Queensland Library Services plan, design and deliver a training program comprising seven individual components including induction training, individual instruction, group training, and regional office training. The program is guided by a formal, detailed training plan developed by experienced library trainers. Training needs assessment however has been informal and infrequent. Library Services commenced a formal training needs analysis (TNA) in 2014. It was designed to gather evidence for decision making around future training activities. Methods – The TNA was comprised of five quantitative and qualitative components: analysis of catalogue and knowledge management database usage statistics; analysis of paid subscription usage statistics; analysis of library reference and research request data; work shadowing library clients; and interviews with selected team managers. Results – Each component revealed different aspects of our clients’ training needs. The results of the TNA revealed gaps in current training and education services, and opportunities for maximizing the effectiveness of our training program. The TNA also provided infrmation about our products and services beyond implications for training. Conclusion – As a result of the TNA the LAQ library has made changes to it training activities, which we believe are now more closely aligned with client needs and organizational objectives than they were in the past.